2013
DOI: 10.1063/1.4824291
|View full text |Cite
|
Sign up to set email alerts
|

Raman measurements of uniaxial strain in silicon nanostructures

Abstract: The strain-shift coefficient used to convert Raman shifts to strain depends on multiple factors including phonon deformation potentials (PDPs). PDPs have been reported for silicon, which differ by 30%. This leads to varying strain-shift-coefficients. Using the wrong strain-shift coefficient affects the strain determined. The discrepancies in the reported PDPs were previously ascribed to surface stress relaxation and the opacity of the material to the laser radiation. This paper shows that surface orientation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Application of stress to the NW causes a shift of the first order optical phonon peak of Si at 520.2 cm –1 linearly dependent on the strain. 40 These typical shifts to lower wave numbers of a strained NW integrated in the TSD and, for comparison, bulk Si are shown in Figure 3 a. The inset shows the relationship between the Raman signal peak shift and thereof calculated strain values of the NW.…”
mentioning
confidence: 88%
“…Application of stress to the NW causes a shift of the first order optical phonon peak of Si at 520.2 cm –1 linearly dependent on the strain. 40 These typical shifts to lower wave numbers of a strained NW integrated in the TSD and, for comparison, bulk Si are shown in Figure 3 a. The inset shows the relationship between the Raman signal peak shift and thereof calculated strain values of the NW.…”
mentioning
confidence: 88%
“…bulge testing) (El Kurdi et al, 2010a;Sánchez-Pérez et al, 2011;Boztug et al, 2013). Strain measurements are usually done by micro-Raman spectroscopy (El Kurdi et al, 2010a;Boztug et al, 2013;Ghrib et al, 2013;Ureña et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The strain levels were verified by scanning electron microscopy (SEM) and Raman spectroscopy and compared with analytical calculations and finite element simulations. 33,34 The silicon crystal structure of the samples was also analyzed and concluded that it has not been compromised. 34 Strain determined by SEM was carried out by measuring the displacement of a mobile cursor fabricated alongside the silicon beams with respect to a fixed cursor positioned at the substrate sidewalls.…”
Section: Methodsmentioning
confidence: 99%
“…33,34 The silicon crystal structure of the samples was also analyzed and concluded that it has not been compromised. 34 Strain determined by SEM was carried out by measuring the displacement of a mobile cursor fabricated alongside the silicon beams with respect to a fixed cursor positioned at the substrate sidewalls. Additional details of the fabrication process and strain characterization can be found in Refs.…”
Section: Methodsmentioning
confidence: 99%